Transforming Norms : Legal Design, Plain Language and AI for Personalized Law - Toivonen, Nina; Ketola, Anne; Haapio, Helena (Padova university press, 2025)
What good is a law if its subjects are unaware of its existence or impact? As personalized law – legal rules tailored to individual circumstances – emerges as a transformative paradigm, it is crucial to critically assess both its promises and pitfalls. Going beyond the traditional one-size-fits-all approach, personalized law aims to improve fairness and efficiency in legal systems by taking individuals’ personal traits into account in the creation of legal solutions with the help of Big Data and AI. In line with this Special Issue’s focus on the construction of the socio-digital world, this article offers a perspective to personalized law through the lens of legal design, with a particular emphasis on the proactive law and plain language paradigms that inform it. The article discusses some of the key challenges of personalized law, such as the regulatory complexity and opacity that individualized legal rules can introduce and suggests that the most practical potential of personalized law lies in personalizing legal communication and establishing mechanisms for self-personalization of norms. It is highlighted that for the maintenance of legal certainty and the protection of privacy and autonomy, tailoring legal solutions with AI should not happen as a top down, control-and-command type of rulemaking, but rather through using self-regulative and co-regulative strategies. Drawing from information design and plain language literature, the article proposes that personalized accessibility to legal communication should build on three elements: 1) user- centered communication, 2) clear communication and information design principles and 3) the responsible use of AI tools. By doing so, the article argues for personalized law that enables people to act upon their rights and obligations in their individual circumstances based on comprehension and agency.
Keywords: artificial intelligence (AI); legal design; personalized law; plain language; fi=Talousoikeus|en=Business Law|